CAMPURAN SAGU DAN ILES-ILES SEBAGAI EKSTENDER PEREKAT UREA FORMALDEHIDA KAYU LAPIS - Suwardi Sumadiwangsa; Yusuf Sudo Hadi; Jhon Novarly Simanjuntak; Suwandi Kliwon (Jurnal Penelitian Hasil Hutan, 1987)
In 1984 Indonesia required more than 64.000 ton of wheat flour for  extender  of urea formaldehyda   (UF) adhesive in plywood  industry.  It is considered more economical  when the wheat flour  can be substituted  by locally available carbohydrate  such as sago (Metroxylon  sp.). However, sago alone gives poor quality  as an extender  of  UF adhesive.Iles-iles (Amorphophallus oncophyllus)  is another potential source of carbohydrate.   This contains  more protein  and mannan  than that  of wheat flour. Therefore, it is deemed necessary to explore the posisibility  of mixing sago and iles-iles as a combined  substitute  for  wheat flour  as extender  of  UF adhesive.This work is intended to obtain optimal ratio of sago and iles-iles formulation,   and then to compare its performance  with that of wheat flour extender.  This study comprise of 5 levels of sago and iles-iles mixed and 3 levels of flour  extender, each of which were having 5 replicates aplied for plywood  adhesion.The 713 ratio of sago and iles-iles is the same as, if not better than, wheat flour  extender.  The extender content  (X) and plywood  bonding strength (Y) for  each of  the extender  was linearly correlated.  It is interesting to note  that  the 614 ratio gives  very small slope (B) in its linear regression, in contrast  to the others.Although  the price of iles-iles was comparable to the wheat flour's, the lles-iles gives higher bonding strength  at lower proportion  compared with that of  the wheat flour  extender.